Средства и методы с урдопедагогической работы с детьми, подлежащими кохлеарной имплантации - Арутюнян, И. А.
In the article, on the basis of work experience and research reveals the basic means and methods of surdopedagogical work with children, before cochlear implantation and provide psychological support to their parents.
Keywords: Кохлеарная имлантация